The taxonomy and osteology of fishes of the family Tripterygiidae (Perciformes : Blennioidei) of South Africa - Holleman, Wouter (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1979)
This study is divided into two parts. The first deals with the taxonomy of the South African fishes of the Tripterygiidae. The second part describes the osteology of one genus of the family, and draws comparisons with the other genera discussed in this study. Five genera of Tripterygiidae are recognized from South African waters. Cremnochorites, a monotypic genus, is described as new. The single species, C. capensis, has been recorded only from the southern and south-eastern coast of South Africa. It is distinguished from other genera by a combination of features which includes scalation, dorsal and anal fin spine counts, and various osteological characters. Three genera, Norfolkia Fowler, Helcogramma McCulloch & Waite, and Enneapterygius Rüppell occur throughout most of the Indo-Pacific. A single species of Norfolkia, N. springeri Clark (in press) is found in Zululand. Two species are ascribed to Helcogramma, H. obtusirostre (Klunzinger) and H. fuscopinna sp.n. Parallels are drawn between two species of Tripterygion Risso, T. tripteronotus and T. delaisi from the Mediterranean. The two South African Helcogramma species show similar depth preferences to the two Tripterygion species, resulting in similar morphological differences between the two species of each pair. The genus Enneapterygius Rüppell is divided into two genera, Enneanterygius and Scoliosolen gen.n. The division is based on the form of the supraoccipital sensory canal and associated osteological characters. Sooliosolen has a crescent-shaped supraoccipital canal and cranial osteology similar to the majority of other tripterygiid genera, whereas Enneapterygius has a 'U'-shaped supraoccipital canal which curves around the first dorsal fin, a comparatively long, concave supraoccipital bone which extends anteriorly between the parietal and between the posterior ends of the frontals. Two species are referred to Scoliosolen, S. abeli (Klausewitz) and S. conspicuus (Clark), and two new species are described for Enneapterygius, E. pulcherrimus and E. trianeulus. A literature survey revealed little consistency in ascribing species to any particular genus. Thus, throughout this study an attempt is made to define the genera so that future confusion can be avoided. In the light of these definitions an assessment is made of the original descriptions of a large number of species to determine which of the species can be ascribed to Norfolkia and to Helcogramrna. This has been possible to a lesser degree for Enneapterygius and Scoliosolen, for the major external feature separating these two genera, the shape of the supraoccipital sensory canal, is described only for Red Sea (Clark, in press) and South African species (this study). This study places four species in Enneapterygius, and six in Scoliosolen. To provide a firmer foundation for defining the genera, an investigation was made of the osteology of Scoliosolen conspicuus. Enneapterygius was originally chosen for the osteolofical study as it is reputedly the largest genus of the family, and thus likely to be the most generalized. Once comparisons had been made with other Enneapterygius species, it became apparent that this genus had to be divided into two genera, Enneapterygius and Scoliosolen. It is not known whether Scoliosolen is the largest genus, but it is likely to be one of the largest once a complete survey of the species originally ascribed to Enneapterygius has been undertaken. Finally, an osteological comparison is made of the five genera which occur in South African waters to provide firmer bases for the generic definitions. Only those characters which appear to be constant within a genus are used. Reference is made to a number of genera which do not occur in South African waters, to ensure that the characters chosen cannot be applied to other genera
Keywords: Tripterygiidae -- South Africa; Blennioidei -- South Africa